Checkpoint and DNA-repair proteins are associated with the cores of mammalian meiotic chromosomes. - Tarsounas, M; Moens, P (2001)
Meiotic checkpoints are manifested through protein complexes capable of detecting an abnormality in chromosome metabolism and signaling it to effector molecules that subsequently delay or arrest the progression of meiosis. Some checkpoints act during the first meiotic prophase to monitor the repair of chromosomal DSBs, predominantly by meiotic recombination, or to ensure the correct establishment of synapsis and its well-timed dissolution. In mammals, a number of checkpoint and repair proteins localize to the meiotic chromosomal cores, sometimes in the context of the synaptonemal complex (SC). Here we discuss possible functions of these proteins in the accomplishment of meiotic recombination and normal progression of the meiotic pathway. Also, we present arguments for a structural role of cores and SCs in the assembly of the repair and checkpoint protein complexes on the chromosomes.